SELEKSI UJIAN ONLINE DALAM PENERIMAAN SISWA BARU DI SEKOLAH MENENGAH KEJURUAN (SMK) - Acmad Nurhadi; Elly Indrayuni (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2019)
Acceptance of new students is one of the processes that exist in educational institutions such as schools that are useful for screening selected students according to the criteria determined by the school to become students of their students. In general, the process of admitting new students is done through the stages of registration, selection tests, and student admissions. In this study its application to the Vocational High School which has been done manually or already computerized but uses Microsoft Office Excel, which allows there is still a lot of lack of data, manual calculation of test scores that allows errors. The formulation of the problem from this research is how to create an information system for admitting new students to Vocational Schools. The research method used is literature, observation, design, trial and implementation. This new student admission information system is built with the PHP programming language and utilizes the MySQL database as a database server and Waterfall in general. Stages in the waterfall include, analysis of software requirements, design, programming code, testing, support. The results of this study are new webbased student admission information systems that have the ability to make it easier for parents and new prospective students to obtain all information about admitting new students and conducting the online registration process.